Abnormal arm swing movements in Parkinson’s disease: onset, progression and response to L-Dopa - M. Patera; A. Zampogna; L. Pietrosanti; F. Asci; M. Falletti; G. Pinola; E. Bianchini; G. Di Lazzaro; V. Rosati; P. Grillo; F. Giannini; F. Fattapposta; et al. (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Reduced arm swing movements during gait are an early motor manifestation of Parkinson’s disease (PD). The clinical evolution, response to L-Dopa and pathophysiological underpinning of abnormal arm swing movements in PD remain largely unclear. By using a network of wearable sensors, this study objectively assesses arm swing movements during gait in PD patients across different disease stages and therapeutic conditions. Methods Twenty healthy subjects (HS) and 40 PD patients, including 20 early-stage and 20 mid-advanced subjects, underwent a 6-m Timed Up and Go test while monitored through a network of wearable inertial sensors. Arm swing movements were objectively evaluated in both hemibodies and different upper limb joints (shoulder and elbow), using specific time-domain (range of motion and velocity) and frequency-domain measures (harmonics and total harmonic distortion). To assess the effects of L-Dopa, patients under chronic dopaminergic therapy were randomly examined when OFF and ON therapy. Finally, clinical-behavioral correlations were investigated, primarily focusing on the relationship between arm swing movements and cardinal L-Dopa-responsive motor signs, including bradykinesia and rigidity. Results Compared to HS, the whole group of PD patients showed reduced range of motion and velocity, alongside increased asymmetry of arm swing movements during gait. Additionally, a distinct increase in total harmonic distortion was found in patients. The kinematic changes were prominent in the early stage of the disease and progressively worsened owing to the involvement of the less affected hemibody. The time- and frequency-domain abnormalities were comparable in the two joints (i.e., shoulder and elbow). In the subgroup of patients under chronic dopaminergic treatment, L-Dopa restored patterns of arm swing movements. Finally, the kinematic alterations in arm swing movements during gait correlated with the clinical severity of bradykinesia and rigidity. Conclusions Arm swing movements during gait in PD are characterized by narrow, slow, and irregular patterns. As the disease progresses, arm swing movements deteriorate also in the less affected hemibody, without any joint specificity. The positive response to L-Dopa along with the significant correlation between kinematics and bradykinesia/rigidity scores points to the involvement of dopaminergic pathways in the pathophysiology of abnormal arm swing movements in PD.